Induction of skeletal abnormalities and autophagy in Paracentrotus lividus sea urchin embryos exposed to gadolinium. (September 2017) - Martino, Chiara; Chiarelli, Roberto; Bosco, Liana; Roccheri, Maria Carmela
Abstract: Gadolinium (Gd) concentration is constantly increasing in the aquatic environment, becoming an emergent environmental pollutant. We investigated the effects of Gd on Paracentrotus lividus sea urchin embryos, focusing on skeletogenesis and autophagy. We observed a delay of biomineral deposition at 24 hours post fertilization (hpf), and a strong impairment of skeleton growth at 48 hpf, frequently displayed by an asymmetrical pattern. Skeleton growth was found partially resumed in recovery experiments. The mesodermal cells designated to biomineralization were found correctly migrated at 24 hpf, but not at 48 hpf. Western blot analysis showed an increase of the LC3-II autophagic marker at 24 and 48 hpf. Confocal microscopy studies confirmed the increased number of autophagolysosomes and autophagosomes. Results show the hazard of Gd in the marine environment, indicating that Gd is able to affect different aspects of sea urchin development: morphogenesis, biomineralization, and stress response through autophagy. Highlights: The effects of gadolinium were evaluated on Paracentrotus lividus sea urchin embryos. We observed a strong impairment of skeleton growth and patterning. The mesodermal cells designated to biomineralization were not correctly located. Autophagy was found strongly induced as a cell survival mechanism. The results confirm the hazard of Gd in the marine environment.